2019
DOI: 10.3390/ijerph16173158
|View full text |Cite
|
Sign up to set email alerts
|

Research on Relationships between Sexual Identity, Adverse Childhood Experiences and Non-Suicidal Self-Injury among Rural High School Students in Less Developed Areas of China

Abstract: Purpose: The objective of this study was to examine the influence of sexual identity and adverse childhood experiences (ACEs) on non-suicidal self-injury (NSSI) among rural high school students in less developed areas of China. Methods: Behavior risk factors data collected from 1810 students from a high school in Jiangxi province, China. Five measures of childhood abuse and household dysfunction were summarized, and ACE was divided into 0, 1, 2, 3–5 ACEs. Logistic regression analysis was used to explore the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
3
14
0
8
Order By: Relevance
“…It also expanded upon the research on this aspect of rural primary and middle school students in developing areas of China. Consistent with previous research, primary and middle school students who have suffered school bullying and have psychological problems have a higher risk of NSSI [22,27,28]. In addition, the bootstrap test of this study showed that the psychological problems of rural primary and middle school students in developing areas of China play a mediating role between school bullying and NSSI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It also expanded upon the research on this aspect of rural primary and middle school students in developing areas of China. Consistent with previous research, primary and middle school students who have suffered school bullying and have psychological problems have a higher risk of NSSI [22,27,28]. In addition, the bootstrap test of this study showed that the psychological problems of rural primary and middle school students in developing areas of China play a mediating role between school bullying and NSSI.…”
Section: Discussionsupporting
confidence: 89%
“…Due to the lack of effective parental supervision and limited educational resources, left-behind youth may not be able to properly resolve life's difficulties or to properly be able to learn to do so and may, as a result, suffer a series of serious health risk behaviors. Compared to children who were non-left-behind (rural, school-aged youth who indicated that neither of their parents worked elsewhere in China ) in Jiangxi Province, the "left-behind" youth were more likely to suffer from a higher rate of school bullying, psychological problems, and NSSI behaviors [21,22]. Previous studies have shown that school bullying and psychological problems may have an impact on NSSI [20], and school bullying also increases the occurrence of adolescent psychological problems [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bullying is a highly stressful experience and victims can have numerous negative outcomes (Duong and Bradshaw, 2014). Peer bullying experienced by adolescents is correlated with severe mental health problems – including suicidal ideation, suicide attempts, non-suicidal self-injury, depression and anxiety – and can have long-term detrimental life consequence (Klomek et al ., 2007; Drydakis, 2019; Li et al ., 2019; Chen et al ., 2020). Due to the marginalised sexual orientation, lesbian, gay and bisexual (LGB) adolescents are more likely to face noticeable challenges and adverse experiences, including the victim-bully cycle (Button et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Determinadas identidades de gênero que não se adaptam a estas regras são consideradas defeitos do desenvolvimento ou impossíveis de existir dentro dessa lógica, o que provoca sofrimento que pode levar ao adoecimento. Estudo realizado na China com 1810 estudantes de ensino médio Research, Society and Development, v. 9, n. 10, e9019109364, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.9364 evidenciou associação estatisticamente significativa entre identidade lésbica, gay e bissexual e autolesões não suicidas (Li et al, 2019).…”
Section: Discussionunclassified
“…Indivíduos das minorias sexuais estão mais expostos a experiências adversas na infância e a autolesões do que os heterossexuais (Li et al, 2019).…”
Section: Introductionunclassified